Analyzing the Effectiveness of an Educational Process for Teaching Programming Through Educational Robotics in a Brazilian Technical and Vocational High School - Souza, Isabelle M. L.; Sampaio, Lívia M. R.; Andrade, Wilkerson L. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2023)
Problem-solving is an essential human development skill that can be fostered through Computational Thinking (CT). Programming education has been explored to develop CT in High Schools. However, teaching programming can be challenging, being necessary educational processes that improve guidelines to direct this teaching. In the past, we proposed an educational process based on methods for teaching programming with Educational Robotics (ER) and the Anthropological Theory of Didactics. However, we still need to conclude the effectiveness validation of this educational process. This study aims to evaluate our educational process’s effectiveness in developing Technical and Vocational High School students’ CT skills. We intend to answer the research question: RQ) How effective is the impact of an educational process of teaching programming with ER on students’ CT skills in High School? The development of CT skills was evaluated through the Román-Gonzalez CT Test. The overall results indicated that the educational process is effective in teaching programming with ER impacting CT skills. This study’s result contributes to the scientific community in the sense of guiding the validation of an educational process.